Participant views on practical considerations for feedback of individual genetic research results: a case study from Botswana. Issue 1 (31st December 2023) - Ralefala, Dimpho; Kasule, Mary; Matshabane, Olivia P.; Wonkam, Ambroise; Matshaba, Mogomotsi; de Vries, Jantina
ABSTRACT: Key to discussions around feedback of individual results from genomics research are practical questions on how such results should be fed back, by who and when. However, there has been virtually no work investigating these practical considerations for feedback of individual genetic results in the context of low-and middle-income countries (LMICs), especially in Africa. Consequently, we conducted deliberative focus group discussions with 6 groups of adolescents ( n = 44) who previously participated in a genomics study in Botswana as well as 6 groups of parents and caregivers ( n = 49) of children who participated in the same study. We also conducted in-depth interviews with 6 adolescents and 6 parents or caregivers. Our findings revealed that both adolescents and parents would prefer to receive their individual genetic results in person, with adolescents preferring researchers to provide feedback, while parents preferred doctors who are associated with the study. Both adolescents and parents further expressed that feedback should be supported by counselling but differed on the timing of feedback, with preferences ranging from feedback as quickly as possible to feedback at project end. In conclusion, decisions on practicalities for feedback of results should be done in account of participants' context and considerations of participants' preferences.